ANALISIS PORTOFOLIO ASET BANK SYARI`AH DAN BANK KONVENSIONAL DI INDONESIA - DWI PITRADITYA, VIVIANA Dwi (Jurnal Akuntansi AKUNESA, 2013)
Banks in Indonesian consists of two syari`ah bank based and convetional bankbased. Islamic bank in Indonesia to experience growth and significant growthovertime. Portofolio assets of islamic banks and conventional banks in Indonesiaare very influential in the Indonesia economy. With a portofolio of assets betweenIslamic banks and conventional banks cank work together to advence the bankingsystem and economy system in Indonesia today. Even no difference is toosignificant and in the selection of banks, whether Islamic banks and conventionalbanks.Keywords : portofolio assets, conventional banking, Islamic banking.